FORMATION OF MAIZE HYBRIDS GRAIN PRODUCTIVITY DEPENDING ON SOWING RATE - Zhemela, H. P.; Barabolia, O. V.; Liashenko, V. V.; Liashenko, Ye. S.; Podoliak, V. A. (Scientific Progress & Innovations, 2021)
Maize is universal due to its using as fodder, technical and food crop, which determines the topicality of increasing its productivity both in Ukraine and around the world. The aim of the article was to study the de-pendence of grain productivity of maize hybrids on sowing rates. In the process of research, field and quanti-tative methods, observation, and calculation method were used. Our research has shown that on the average over the study years, the minimum growing season was observed in P8521 early-maturing hybrid – 122.8 days, the longest – in PR38N86 mid-ripening – 131.1–133.7 days, in PR39B76 mid-early ripening – 125.4–127.5 days. The duration of interphase periods and the growing season of maize hybrids depended on their biological characteristics and weather conditions and almost did not change under the influence of plant density. It has been determined that according to biological features of mid-ripening crop hybrid higher plants were formed than in early-ripening hybrids. With increasing the density of the above mentioned hy-brids, a decrease in plant height by 2.7, 3.4 and 3.3 cm, respectively, was observed. Thus, in the panicle flowering phase, when maize plants reached their maximum height, in the wet year it grew from sparse to overcrowded crops, and in the arid year it decreased. The studies have shown that individual productivity indicators decrease at overcrowding. In our opinion, the main reserve for increasing the production of com-mercial grain is determining the optimal density for maize hybrids of different ripening groups, taking into account agro-ecological conditions. The optimal number of maize ears, at which indicators of individual productivity and the number of plants per area unit are best combined, was achieved in P8521early-ripening hybrid in the variants with plant density of 75 thou/ha, in PR39B76 mid-early ripening – 70 thou/ha, and PR38N86 mid-ripening– 70 thou/ha.